Update to figure 1 in "Macroeconomic Shocks and their Propagation" - Edoardo Chiarotti (Graduate Institute of International and Development Studies, 2021)
This note proposes an update to Figure 1 in "Macroeconomic Shocks and their Propagation" in the Handbook of Macroeconomics of 2016 (Ramey, 2016). Figure 1 of Ramey (2016) reports Impulse-Response Functions (IRFs) of variables of interest to a shock in the Federal Funds Rate, following the baseline and variations of the Vector Autoregression (VAR) models in Christiano et al. (1999). This note shows that, when using a time series for FED non-borrowed reserves that is not corrected for regulatory changes in reserve requirements, the results for the period 1983-07 are robust to the inclusion of monetary variables.
Keywords: E52; E58; E65; 330; Central Bank; FED Reserves; VAR